2016
DOI: 10.1080/15384101.2016.1181239
|View full text |Cite
|
Sign up to set email alerts
|

Roles of actin binding proteins in mammalian oocyte maturation and beyond

Abstract: Actin nucleation factors, which promote the formation of new actin filaments, have emerged in the last decade as key regulatory factors controlling asymmetric division in mammalian oocytes. Actin nucleators such as formin-2, spire, and the ARP2/3 complex have been found to be important regulators of actin remodeling during oocyte maturation. Another class of actin-binding proteins including cofilin, tropomyosin, myosin motors, capping proteins, tropomodulin, and Ezrin-Radixin-Moesin proteins are thought to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 179 publications
(288 reference statements)
2
27
0
Order By: Relevance
“…These results firmly suggest that treatment with compound 4 impairs the formation of meiotic spindles during mouse oocyte maturation. Considering previously described roles of PLK1 in meiotic spindle formation, the results of the present study strongly suggest that the inhibitory effect of macrocyclic compound 4 results in the inhibition of PLK1, and therefore causes depletion of MTOC formation.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…These results firmly suggest that treatment with compound 4 impairs the formation of meiotic spindles during mouse oocyte maturation. Considering previously described roles of PLK1 in meiotic spindle formation, the results of the present study strongly suggest that the inhibitory effect of macrocyclic compound 4 results in the inhibition of PLK1, and therefore causes depletion of MTOC formation.…”
Section: Resultssupporting
confidence: 81%
“…Treatment with 4 also increases the fraction of oocytes with al arge polar body (13.7 %, n = 27/196), i.e.,p olar bodies > 50 %o ft he oocyte's diameter,w hereas none of the untreated oocytes showeda bnormally large polar bodies( 0%, n = 0/120). Considering that larger polar body or af ailure of asymmetricd ivision is caused by defects in spindle migration, [17] theser esults suggestt hat treatment with 4 negatively affects spindle migration during oocyte maturation.…”
Section: Biological Evaluationsmentioning
confidence: 90%
“…The increased PB size and symmetric division of oocytes is one of the main phenotypes associated with spindle migration failure during meiosis I (24). Therefore, we performed time‐lapse microscopy to investigate the effects of FLNA knockdown on spindle migration and PBE.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic changes in the actin network are essential in cortex migration of the spindle and cortical polarity to ensure asymmetric division during meiotic maturation. The characteristic feature of these processes is the dynamic transition between monomeric G‐actin and filamentous F‐actin, which is tightly regulated by a large number of actin‐binding proteins (24). Recent studies have revealed the roles of many actin‐binding proteins in oocyte maturation; however, most of their functions remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…17 The roles of microfilaments and/or microtubules in spindle migration and anchorage to the oocyte cortex have been reported for various invertebrate and mammalian oocytes, 2 and several factors have recently been shown to regulate oocyte polarity and asymmetric division. [18][19][20][21] However, the role of centrosomes in this process is still not well understood. We showed that depletion of centriolin caused a failure of peripheral meiotic spindle migration and polarity establishment in a high proportion of oocytes, as well as elongated central spindles, leading to symmetric divisions, as indicated by the production of 2 same-sized cells or the formation of a large polar body.…”
Section: Discussionmentioning
confidence: 99%